A La Tène grave at Spodnja Slivnica near Grosuplje - Šribar, Vinko (Arheološki vestnik, 1957)
On the occasion of digging for foundation of a dung pit in the small castle of Zavrh, of Spodnja Slivnica a cremation grave was excavated with the following contents: 2 ceramic vessels on the ground, 2 iron points of a lance, a big iron knife, 2 armlets made of bronze, 2 fibulae of bronze, 1 ceramic whorl and 6 parts and parcels of a vessel made of bronze plate. The lance points were placed crosswise between the vessels. As there are, for the lance points, more analogies in the pre- La Lène material of Lower Carniola we must not exclude the possibility of having to do with Illyrian indigenous. The inventory is now in the National Museum of Ljubljana. As to the ground the find is rather isolated and therefore an important contribution to the research into the La Tène epoch of Lower Carniola.